Long-Term Follow-Up of the Prospective Randomized AATT Study (Autologous or Allogeneic Transplantation in Patients With Peripheral T-Cell Lymphoma) - Tournilhac, Olivier; Altmann, Bettina; Friedrichs, Birte; Bouabdallah, Kamal; Leclerc, Mathieu; Cartron, Guillaume; Turlure, Pascal; Reimer, Peter; Wagner-Drouet, Eva; Sanhes, Laurence; Houot, Roch; Roussel, Murielle; et al. (Journal of clinical oncology, 2024)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. - Primary analysis of the phase III randomized AATT study showed that younger patients with peripheral T-cell lymphoma (PTCL) consolidated with autologous or allogeneic transplantation (alloSCT) had similar event-free survival (EFS) and overall survival (OS). Seven-year EFS of patients randomly assigned to alloSCT was 38% (95% CI, 25 to 52) compared with 34% (95% CI, 22 to 47) for patients randomly assigned to autologous transplantation of hematopoietic stem cells (autoSCT); OS was 55% (95% CI, 41 to 69) and 61% (95% CI, 47 to 74). Among patients undergoing alloSCT (n = 26) or autoSCT (n = 41) on study, the cumulative progression/relapse rate was 8% (95% CI, 0 to 19) and 55% (95% CI, 35 to 74). Nonrelapse mortality (NRM) was 31% (95% CI, 13 to 49) and 3% (95% CI, 0 to 8) after alloSCT and autoSCT, respectively. Fifteen of 30 patients with early progression and 11 of 20 patients with progression/relapse after autoSCT received alloSCT. Seven-year OS after salvage alloSCT was 61% (95% CI, 47 to 74); NRM was 23% (95% CI, 6 to 40). Long-term follow-up documents the strong graft versus lymphoma effect of alloSCT independent of the timing of transplantation. Survival of patients unable to undergo transplantation was dismal. AlloSCT is the treatment of choice for younger, transplant-eligible patients with relapsed/refractory PTCL. AlloSCT is currently not recommended as part of first-line consolidation.